CATCH EFFICIENCY OF TRAWLERS OFF RATNAGIRI COAST OF MAHARASHTRA, INDIA - B. R. KHARATMOL; LATHA SHENOY; V. V. SINGH (The Bioscan, 2024)
The present study on the catch efficiency of commercial multi-day and single-day trawlers operated off Ratnagiri coast showed that fishing operations were conducted between 15º53’ 24"N to 17º22’36"N latitude and 73º25’ 48"E to 72º 22’ 36"E longitude in the depth range of 10 to 45 m. It clearly indicated that average catch by multi day trawlers was more (43.44kg/ hour) compared to single-day trawlers (35.05 kg/ hour) while average discard by multi-day and single-day trawlers was 7.54kg/ hour to 3.50 kg/ hour respectively. The study showed that single-day trawlers were better in terms of reduced discard rate. Cod end mesh size of trawl net varied from 15 to 30 mm depending on the fishery resources harvested. The study revealed that there was a decrease in the catch per hour per trawler with a decrease in the number of species reported compared to the previous year along the Ratnagiri coast.